THE IMPLEMENTATION OF INTERNATIONAL HEALTH REGULATIONS 2005: A NORMATIVE STUDY OF ROLE OF THE WORLD HEALTH ORGANIZATION WITHIN UNITED NATIONS MISSION FOR EBOLA EMERGENCY RESPONSE IN PREVENTING THE - Zuhdan Fuad Reisnansyah (FH IH 16 UMY 058, 2016)
Ebola Virus Disease (EVD) formerly known as Ebola hemorrhagic fever is a severe, often fatal illness in humans. The current outbreak in West Africa which the first notified in March 2014 is the largest and most complex Ebola outbreak since the Ebola virus was discovered in 1976. World Health Organization (WHO) as a world leader for international public health has a role in preventing the disease. Furthermore, to assist the WHO in terms of response, United Nations (UN) established United Nations Mission for Ebola Emergency Response (UNMEER) on 19 September 2014. In addition, the International Health Regulation (IHR)2005 as an international legal instrument is a rule that has a purpose and scope to prevent, protect against, control and provide a public health response to the international spread of disease. The aims of this research is to know whether the implementation of the International Health Regulation (IHR) 2005 in preventing the Ebola Virus Disease which is by WHO within UNMEER run effectively or not. The type of this research is a normative legal research with statute approach and analytical approach. By using a descriptive qualitative, this research analyzes the implementation of that regulation in preventing the Ebola virus disease by WHO within UNMEER. The result of this research shows that WHO did not carry out its roles properly under the IHR 2005, particularly in term of prevention the Ebola virus outbreak. At the time UNMEER was dissolute, it indicated that UNMEER had achieved their goals, in fact after the dissolution; there were still some confirmed-suspects of Ebola virus in Sierra Leone. The researcher has suggestion that UN should re-establish the existence of UNMEER in preventing and eradicating Ebola virus diseases which are categorized into communicable dangerous diseases. Keywords: Ebola Virus Disease, World Health Organization, UNMEER, International Health Regulation 2005